Environmental & architectural phenomenology. Vol. 10, issue 2 - (:unkn) unknown (Kansas State University. Architecture Department, 1999)
Vol. 10, No. 2, Spring 1999 (includes “items of interest,” "citations received,” book reviews of Edward Casey's The Fate of Place & Clare Cooper Marcus' The House as Mirror of Self, essay by Carol H. Cantrell, and poems by Judyth Hill, Timothy Eiler & Sheryl L. Nelms).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals